ANALYSIS OF LOCATION SUITABILITY IN LOMBOK ISLAND WATERS FOR THE DEVELOPMENT OF Gracilaria sp. SEAWEED CULTIVATION - Tarmizi, Arbi; Diniarti, Nanda (Jurnal Media Akuakultur Indonesia, 2022)
Seaweed is a biological resource that has been used by the Indonesian people as a livelihood. Types of Gracilaria sp. is one of the widely cultivated seaweeds, including on the island of Lombok, West Nusa Tenggara. Seaweed (Gracilaria sp.) is a leading commodity in the fishery sector which has considerable opportunities in the field of cultivation. The quality of the waters in the waters that are still extensive and suitable for aquaculture will support the production of seaweed. Gracilaria sp. seaweed cultivation activities. has been done for a long time but has not yet studied the suitability of water quality as a condition for supporting growth. This research was conducted in April-May 2022 to analyze water quality (temperature, salinity, brightness, depth, dissolved oxygen, pH, nitrate, phosphate, chlorophyll. The results of the research is expected to be a source of information on the influence of gracilaria seaweed cultivation on appropriate water quality. This study aims to determine the level of suitability of waters based on physical and chemical conditions for seaweed cultivation locations in the waters of Ekas Bay, Malacca Bay and West Sekotong. The results are expected to be a source of information and can used as a reference by the community or local government in the development of seaweed cultivation activities.The results showed that the waters of Ekas Bay, Malacca Bay and West Sekotong were included in the category according to the score obtained in the range of 66-78.